(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
The purpose of the study was to design a framework to return a vulnerable girl child in selected single-sex public secondary schools. The study adopted a descriptive phenomenology research design. This study, utilizing purposive stratified sampling selected a total of 32 vulnerable girls from the four selected single-sex girls’ secondary schools. It then selected one Counselling and Guidance teacher from each of the four schools giving a sample size of 4 teachers who were interviewed. Semi-structured interviews with the 32 vulnerable schoolgirl participants involved in the study to complement information collected from secondary data. Data were analysed thematically. These themes were then analysed using the hermeneutical phenomenological technique of Max Van Manen’s Four Life World Existential. The study findings resulted into developing a model. The proposed Christine’s REVUGISS Egg Model offers practical strategies for retaining these girls in school, such as providing educational resources, enhancing parental involvement, offering food programs and sanitary supplies, delivering psychosocial support, strengthening institutional assistance, and increasing financial support. By implementing these measures, schools can create more inclusive and supportive learning environments that empower vulnerable girls to succeed academically and personally. The study recommended that schools should strive to create more inclusive and supportive environments for vulnerable girls. This can be achieved by training teachers on gender sensitivity, implementing strict anti-bullying policies, and establishing a strong and accessible guidance and counselling department within schools.